Cyborgizacja edukacji – próba konceptualizacji - Klichowski, Michał; Przybyła, Mariusz (Wydawnictwo Naukowe UAM, 2013)
The main objective of this article is the conceptualization of the term cyborgization of education and the presentation the project of educational research and analysis of the process of cyborgization. In addition, it shows a general contexts of cyborgization.
Cyborgization of education – an attempt of conceptualization
Keywords: education; cyborgs; cyborgization